VALUASI EKONOMI SUMBERDAYA ALAM TAMAN HUTAN RAYA BUKIT SOEHARTO DI PROVINSI KALIMANTAN TIMUR - Erfan Noor Yulian; Lailan Syaufina; Eka Intan Kumala Putri (Graduate School Bogor Agricultural University (SPs IPB), 2011)
Bukit Soeharto Forest Park at East Borneo Province has benefits for community in around it, not only direct use (tangible benefit) but also indirect use (intangible benefit). In order to identify the economic value benefit of the forest park, calculation of the total economic value of forest park Bukit Soeharto is required. By using productivity, substitution value and contingency approaches, any commodities such as tree, firewood, medicinal plant, fauna, rattan, fruit, honey, vegetables, water, carbon sink, coal, flood control, damage caused by forest fires, forest damage due to illegal logging and forest damage caused by coal mining the forest park, have total economic value of Rp. 141,390,367,264,492.00. This result of the research is expected give input for the Bukit Soeharto forest park community, for them to have high motivation to preserve the existent of the forest. For any stakeholders such as Regional Government, Forest Department, NGO, this research is expected to give inputs for the potential development of Bukit Soeharto forest park. Keyword: valuation, economic, forest park, Bukit Soeharto, benefit, productivity, substitution value contingency